Evaluation of GaN-HEMT power amplifiers using BST-based components for load modulation. Issue 3 (June 2014) - Berroth, Manfred; Jacob, Arne F.; Schmidt, Lorenz-Peter; Arnous, Mhd. Tareq; Wiens, Alex; Saad, Paul; Preis, Sebastian; Zhang, Zihui; Jakoby, Rolf; Boeck, Georg
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper, the concept of load-modulated power amplifiers (PAs) is studied. Two GaN-HEMT power amplifiers (PAs), targeted for high efficiency at maximum and output back-off (OBO) power levels, are designed, implemented, and tested across 1.8–2.2 GHz. The load modulation in the first design is realized by tuning the shunt capacitors in the output matching network. A novel method is employed in the second design, where barium–stronrium–titante is used for the realization of load modulation. The large-signal measurement results across the desired band show 59–70% drain efficiency at 44–44.5 dBm output power for both designs. Using the available tunable technique, the drain efficiency of the PAs is enhanced by 4–20% at 6 dB OBO across the bandwidth.